Aplikasi Media Pembelajaran Sinau Basa Berbasis Android pada Mata Pelajaran Bahasa Jawa Kelas V - Dodi Ghani Setiawan; Sigit Sugiyanto; Tito Pinandita; Hindayati Mustafidah (Sekawan Institut, 2025)
The alpha generation is the generation born in 2010 to 2025. The birth and growth of the alpha generation is surrounded by technology which results in dependence on smartphones. The development of technology also has its urgency in the field of education. The independent curriculum emphasizes teachers to be able to integrate technology with learning media in the process of teaching and learning activities. However, the problems that occur in schools, there are still teachers who have not utilized technology in the learning process, especially in Javanese language subjects. Teachers still use conventional methods and rely on textbooks which results in the lack of enthusiasm of students during the learning process. Therefore, an android-based learning media application was developed with the aim of becoming a creative and innovative teacher's teaching media in delivering subject matter, supporting the independent learning process of fifth grade students of SD Negeri 2 Rajawana, and as a means of discussion between teachers and students. The system developer method used in developing this application is the Multimedia De-velopment Life Cycle (MDLC) which consists of 6 stages (Concept, Design, Material Collection, Manufacture, Testing, and Distribution). Based on black box testing, the Sinau Basa Learning Media Application can run smoothly according to its function on an Android Smartphone. Then, the N-Gain test results show a score of 64%. When referring to the value of g->56-75, it is included in the moderately effective category.